THE 1929 WOMEN RESISTANCE TO COLONIALISM IN EASTERN NIGERIA AND THE QUEST FOR GENDER EQUITY IN NIGERIAN POLITICS - Abah, Norbert Chijioke (Socialscientia: Journal of Social Sciences and Humanities, 2020)
The problem of disparity, particularly gender disparity in political participation has attracted and held the attention of women, feminists and development agencies for a long time. At this 90th anniversary of the 1929 women’s resistance to colonialism in Eastern Nigeria: Aba women’s riot of 1929, we reflect on their heroic past and the status of women in modern Nigerian politics. Relying on documentary materials, this paper interrogates the paradox of current marginalization of women, underlines the power of effective organization and solidarity; and opines that Nigerian women do not have to wait until given power by men before they can participate effectively in politics. The paper thus suggests that women can look back on the 1929 protests and learn lessons that can motivate them to move to reverse their decades of marginalization, discrimination and invisibility in Nigerian politics.